1980
DOI: 10.1152/ajpcell.1980.239.5.c217
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction formation and regulation in myometrium

Abstract: Myometrial tissues from pregnant rats were examined by electron microscopy for the presence of gap junctions after incubation in vitro with a variety of agents. Gap junctions were present in low frequency or absent prior to incubation in vitro. The junctions were present in control tissues in high frequency after 48 h incubation. The addition of cycloheximide or actinomycin D inhibited the incorporation of [3H]leucine into TCA-precipitable proteins and prevented gap junction formation. A prostacyclin analog (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(50 citation statements)
references
References 19 publications
2
46
0
2
Order By: Relevance
“…Indeed, several studies have shown the sensitivity of the myometrium to uterine volume (5) and to stretch (7,30). Another potential complication is the fact that gap junctions that electrically connect myometrial cells may form spontaneously in vitro, which may improve electrical coupling and affect electrical propagation (14,29). Finally, even if a stable pacemaker had been found, there is evidence to suggest that this may not be stable during longer recording periods (26).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown the sensitivity of the myometrium to uterine volume (5) and to stretch (7,30). Another potential complication is the fact that gap junctions that electrically connect myometrial cells may form spontaneously in vitro, which may improve electrical coupling and affect electrical propagation (14,29). Finally, even if a stable pacemaker had been found, there is evidence to suggest that this may not be stable during longer recording periods (26).…”
Section: Discussionmentioning
confidence: 99%
“…The uterus exhibits spontaneous contractile activity which, in both pregnant and nonpregnant females, is maintained relatively quiescent up to labor, at which time it markedly increases in strength, duration, and coordination to permit effective parturition (157,575). In several animal species, including humans, gap junctions and their constitutive connexins are sparsely represented among cells of prelabor myometrium (155)(156)(157)(158)528), a tissue which, at this time, also shows limited coupling, poor spatial propagation of action potentials, and asynchronous contractions (157,158). Gap junctions as well as electrical and metabolic coupling markedly increase, due to a differential modulation of different connexin isoforms between uterine muscle cells during labor and delivery (35, 155-158, 386, 447, 528).…”
Section: Muscular Contractionmentioning
confidence: 99%
“…1982;V crhocff and G ar field, 1986], Prostaglandins seem to directly influence the formation of gapjunctions in the rat [V crhocff and G ar field, 1986]. Prostaglandins may control the aggregation of the structural proteins of the gap junction by effecting cross-linking reactions or by changing the fluidity of the membrane [Garfield et al, 1980b].…”
Section: Discussionmentioning
confidence: 99%